A Philosophical Framework for Enhancing the Understanding of Artefacts in the Technology Classroom. Issue 3 (1st September 2016) - Rauscher, Willem
Abstract : Technology teachers should have a sound understanding and knowledge of artefacts in order to assist learners in the designing, making and evaluating of artefacts. Unfortunately, technology teachers in South African schools seem to have a poor grasp of the complexity of this important part of knowledge that is specific to technology. As a result, many technology teachers are unable to support learners in designing and making artefacts that are functional, aesthetically pleasing and have utility value outside the classroom. This deficiency in their knowledge can, among other things, be attributed to the fact that most technology teachers have not received formal training in technology education. Also, the limited research base and the paucity of subject-based philosophical frameworks in technology education, which could inform classroom pedagogy, exacerbate this situation. Therefore, the purpose of this theoretical essay is to draw on, inter alia, literature from the philosophy of technology to provide an overview of the nature of technical artefacts with a view to creating a framework that will help teachers to understand technical artefacts and be able to teach about them effectively. The framework may be a useful tool for teachers to support learners in designing and making technical artefacts that work properly, are fit-for-purpose, and are well finished. The framework, which provides a structure for designing and developing technical artefacts, may also serve as an instrument to help learners in evaluating existing artefacts, which, in turn, may enhance their understanding of the knowledge that is embedded in artefacts.